2020
DOI: 10.1364/ol.399206
|View full text |Cite
|
Sign up to set email alerts
|

Laser ellipticity-dependent supercontinuum generation by femtosecond laser filamentation in air

Abstract: We experimentally investigate the laser polarization effect on the supercontinuum (SC) generation through femtosecond laser filamentation in air. By tuning filamenting laser ellipticity from linear polarization to circular polarization, the spectral intensity of the SC after filamentation gradually increases, while the spectral bandwidth of the SC continuously decreases. The laser ellipticity-dependent spectral intensity modulation of the SC is stronger at higher filamenting pulse energy. Laser energy deposits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It was demonstrated that the clamped intensity is 4 × 10 13 W/cm 2 for a laser pulse of 100 fs duration from theoretical to experimental observations (Figure 3a) [12,32]. Owing to the clamping of the peak intensity inside the filaments, a constant blue shift of the super-continuum spectrum can be expected for pulse energies above a threshold [33].…”
Section: Intensity Clampingmentioning
confidence: 79%
“…It was demonstrated that the clamped intensity is 4 × 10 13 W/cm 2 for a laser pulse of 100 fs duration from theoretical to experimental observations (Figure 3a) [12,32]. Owing to the clamping of the peak intensity inside the filaments, a constant blue shift of the super-continuum spectrum can be expected for pulse energies above a threshold [33].…”
Section: Intensity Clampingmentioning
confidence: 79%
“…4(b). The measured plasma temperature of the 1000 Hz filament increases by 22% up to ∼6230 K, which is beneficial for plasma filament-related applications, such as air lasing [12] , three harmonic generation [23] , and supercontinuum generation [8] . The measured plasma temperature is in agreement with Ref.…”
Section: Resultsmentioning
confidence: 99%
“…The propagation of powerful femtosecond laser pulses in air is a very complicated phenomenon that involves a number of nonlinear processes, including four-and six-wave mixing [1,2] , odd harmonics [3,4] , self-focusing and filamentation [5] , self-phase modulation [6] , supercontinuum generation [7,8] , and so on. The self-focusing phenomenon during the nonlinear propagation leads to the ionization of air molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic equilibrium between the Kerr self-focusing and plasma-defocusing effects leads to filamentation [1][2][3] . Due to its potential applications in supercontinuum emission [4][5][6] , extreme ultraviolet (EUV) emission [7,8] , air lasing [9,10] , THz radiation [11,12] , remote sensing [13] , guiding of corona discharges [14] , machining [15] and weather control [16] , filamentation of femtosecond laser pulses in optically transparent media has attracted a great deal of attention in recent years. One of the most profound effects during femtosecond filamentation is intensity clamping phenomena.…”
Section: Introductionmentioning
confidence: 99%